Survei Varietas Jagung dan Kesesuaian Tekstur Tanah di Seluruh Unit Agroekologi Cekungan Sungai Watari, Negara Bagian Kano, Nigeria - Muhammad, Hafsat Bala; Umar, Rabiatu Balarabe; Imam, Mahmoud Zubair; Sani, Inuwa Sani; Adamu, Karimatu Umar (PT. Pubsains Nur Cendekia, 2026)
The urgency of optimizing maize (Zea mays L.) productivity in semi-arid regions like the River Watari basin depends heavily on aligning soil physical characteristics with appropriate cultivar selection to ensure regional food security. This study evaluates soil texture and maize cultivar suitability within irrigated agro-ecologies by analyzing 54 soil samples for physicochemical properties, including soil pH, nitrogen, phosphorus, and potassium, exchangeable bases, and organic carbon. The research identified that the area is predominantly characterized by loamy and sandy loam soils, which are moderately suitable for maize production. Seven major cultivars, including hybrid and open-pollinated varieties, were identified. Results reveal clear relationships between soil texture and distribution: hybrid varieties are concentrated in well-drained sandy loam, while early maturing cultivars are common in clay-rich soils with higher moisture retention. These findings emphasize that soil texture critically determines cultivar performance and farmer selection strategies. Integrating soil suitability evaluation into extension services is essential for yield stability and sustainable irrigation planning in northern Nigeria.